Evaluation of Etanercept for Treatment of Reactive Infectious Mucocutaneous Eruption - Miller, Melanie M. (JAMA Dermatol, 2021)
This cohort study evaluates the association of etanercept treatment with outcomes of reactive infectious mucocutaneous eruption in hospitalized children and adolescents.